Effects of Whole‐Body Exposure to Pulsed Electromagnetic Field at Different Frequencies on Knee Osteoarthritis - Yang, Xiaotian; Li, Xuqing; Song, Haixin; Wu, Tao; Li, Jianhua; He, Chengqi (Bioelectromagnetics, 2025)
This study aimed to investigate the efficacy of pulsed electromagnetic field (PEMF) at different frequencies during knee osteoarthritis (OA) progression. Ten‐week‐old male wild‐type (WT) mice undergoing the destabilization of the medial meniscus (DMM) surgery were randomly divided into four groups ( n = 10 each) respectively: DMM, DMM with three PEMF exposure (8, 50, or 75 Hz). PEMF (3.8 mT, 1 h/day) at different frequencies was applied for 4 weeks. Von Frey test, histological assessment, RT‐PCR, immunohistochemical staining, and microcomputed tomography (CT) were performed. PEMF at three frequencies (8, 50, and 75 Hz) decreased the Osteoarthritis Research Society International (OARSI) scores to different extents compared to the DMM group. The mRNA and protein expressions of MMP13 and aggrecan (Acan) in cartilage were improved in three PEMF groups; PEMF at 50 and 75 Hz had better positive effects than PEMF at 8 Hz. The increased synovitis was attenuated by 75 Hz PEMF. 75 and 50 Hz PEMF groups had a beneficial effect on increasing 50% paw withdrawal threshold (PWT) compared with the DMM group. Micro‐CT analysis showed that 75 Hz PEMF group, compared with DMM group, increased trabecular thickness (Tb.Th) of femur and bone volume/total volume (BV/TV) of femoral condyle and femur, and decreased bone surface/bone volume (BS/BV) of tibia. The study demonstrated that PEMF at 75 Hz could attenuate symptomatic and structural knee OA progression. Bioelectromagnetics. 00:00–00, 2025. © 2025 Bioelectromagnetics Society. Whole‐body exposure to PEMF attenuates knee OA progression. PEMF at 75 Hz, compared with 50 and 8 Hz, may have a superior effect on attenuating symptomatic and structural knee OA progression.